Ambroxol modulates 6-Hydroxydopamine-induced temporal reduction in Glucocerebrosidase (GCase) enzymatic activity and Parkinson's disease symptoms - Mishra A.; Chandravanshi L.P.; Trigun S.K.; Krishnamurthy S. (My University, 2025)
Reduced glucocerebrosidase (GCase) enzymatic activity is found in sporadic cases of Parkinson's disease making GCase a serious risk factor for PD. GCase gene mutations constitute a major risk factor in early-onset PD but only account for 5–10% cases. Having enough evidence for construct and face validity, 6-OHDA-induced hemiparkinson's model may be useful to assess the GCase-targeting drugs in order to have new leads for treatment of PD. Ambroxol (AMB) is reported to increase GCase activity in different brain-regions. Therefore, we investigated anti-PD like effects of AMB as well as GCase activity in striatal and nigral tissues of rats in hemiparkinson's model. AMB was given a dose of 400 mg/kg per oral twice daily and SEL used as positive control was given in the dose of 10 mg/kg per oral daily from D-4 to D-27 after 6-OHDA administration. 6-OHDA reduced GCase activity in striatal and in a progressive manner in nigral tissues. AMB and SEL attenuated 6-OHDA-induced motor impairments, dopamine (DA) depletion and GCase deficiency. AMB and SEL also ameliorated 6-OHDA-induced mitochondrial dysfunction in terms of MTT reduction, α-synuclein pathology, loss of nigral cells, and intrinsic pathway of apoptosis by modulating cytochrome-C, caspase-9, and caspase-3 expressions. The results suggest that AMB attenuated 6-OHDA-induced GCase deficiency and PD symptoms. Therefore, the regenerative effects of AMB in dopamine toxicity may be due to its effects on GCase activity and mitochondrial function. Results indicate that SEL also has regenerative effect in the 6-OHDA model. Thus, GCase enzymatic activity is likely to be involved in the development of PD symptoms, and 6-OHDA-induced hemiparkinson's model may be used to evaluate compounds targeting GCase activity for management of PD symptoms. © 2018 Elsevier Inc.